Pengaruh Gaya Kepemimpinan, Kepuasan Kerja dan Motivasi Kerja terhadap Kinerja Guru - Kelly Rozalinda; Fatnan Asbupel (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2026)
Improving teacher performance is a key factor in ensuring the quality of education; however, in practice, various indications of teacher performance problems are still found, influenced by leadership, job satisfaction, and work motivation. This study aims to analyze the influence of principals' leadership style, job satisfaction, and work motivation on teacher performance. The research uses a quantitative approach with a correlational design. Data were collected through structured questionnaires from 67 teachers as the total population and analyzed using multiple linear regression with the assistance of SPSS version 26. The research results indicate that work motivation has a positive and most significant impact on teacher performance, followed by the principal's leadership style, while job satisfaction does not have a significant direct effect. Simultaneously, the three independent variables are able to explain 52% of the variation in teacher performance. This study contributes to strengthening educational management research by emphasizing the importance of enhancing teachers' intrinsic motivation and implementing a participative leadership style as an effective strategy to improve teacher performance at the junior high school level.